Open praxis, open access - Chase, Darren,Haugh, Dana (ALA Editions, 2020)
Part I. Overview of open praxis – Part II. Open access publishing – Part III. Repositories – Part IV. Open educational resources – Part V. Open data.
Literaturangaben
Keywords: Open access publishing; Communication in learning and scholarship; Libraries and electronic publishing; Institutional repositories; Open educational resources